New Options for Managing Weeds in the Landscape - J. Bryan Unruh; Barry J. Brecke (EDIS)
ENH-1039, a 3-page fact sheet by Dr. J. Bryan Unruh and Dr. Barry J. Brecke, describes proper management practices for promoting dense, healthy grass. For situations where these management practices do not suffice, the authors provide descriptions of several new herbicides that are available for use on turfgrasses. Published by the UF Department of Environmental Horticulture, June, 2006.